Remarks at CARE Conference on Gender Equality, Washington, D.C., March 5, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, shares the good news that the governors of the World Bank Group have set ambitious goals to end extreme poverty by 2030 and to boost shared prosperity for the bottom 40 percent of the population in developing countries. He noted that increased economic activity among women has translated into a reduction in poverty by about 30 percent and has helped insulate their households from the recent financial shocks. We need to address our blind spots. We need to draw more attention to the major constraints for women and girls that are right in front of us. Discrimination and prejudice destroy economic opportunity. He reminds us that Malala Yousafzai started a social movement around education for girls first in Pakistan, and then around the world. If we can even begin to move together with that kind of resolve, the world will be more peaceful, more prosperous, more just and worthy of the mothers who gave birth to us.